Mechanisms Causing Acantholysis in Pemphigus-Lessons from Human Skin - Egu, Desalegn Tadesse; Schmitt, Thomas; Waschke, Jens (Frontiers in Immunology, 2022)
Pemphigus vulgaris (PV) is an autoimmune bullous skin disease caused primarily by autoantibodies (PV-IgG) against the desmosomal adhesion proteins desmoglein (Dsg) 1 and Dsg 3. PV patient lesions are characterized by flaccid blisters and ultrastructurally by defined hallmarks including reduction in desmosome number and size, formation of split desmosomes, as well as uncoupling of keratin filaments from desmosomes. The pathophysiology underlying the disease is known to involve several intracellular signaling pathways downstream of PV-IgG binding. Here, we summarize our studies in which we used transmission electron microscopy to characterize the roles of signaling pathways for the pathogenic effects of PV-IgG on desmosome ultrastructure in a human ex vivo skin model. Blister scores revealed inhibition of p38MAPK, ERK and PLC/ Ca2+ to be protective in human epidermis. In contrast, inhibition of Src and PKC, which were shown to be protective in cell cultures and murine models, was not effective for human skin explants. The ultrastructural analysis revealed that for preventing skin blistering at least desmosome number (as modulated by ERK) or keratin filament insertion (as modulated by PLC/ Ca2+) need to be ameliorated. Other pathways such as p38MAPK regulate desmosome number, size and keratin insertion indicating that they control desmosome assembly and disassembly on different levels. Taken together, studies in human skin delineate target mechanisms for treatment of pemphigus patients. In addition, ultrastructural analysis supports to define the specific role of a given signaling molecule in desmosome turnover on the ultrastructural level.